2010
DOI: 10.1002/fam.1041
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characteristic of a novel flame retardant containing phosphorus and its application in poly(ethylene‐co‐vinyl acetate)

Abstract: SUMMARYA novel flame retardant (SPDH) containing phosphorus was synthesized through the reaction of 10-(2,5-dihydroxyphenyl)-9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO-HQ) and synthesized intermediate product 3,9-dichloro-2,4,8,10-tetraoxa-3,9-diphosphaspiro(5.5)undecane-3,9-dioxide (SPDPC). The structure and properties of SPDPC and SPDH were characterized by Fourier transform infrared spectroscopy (FTIR), nuclear magnetic resonance (NMR) spectroscopy and thermogravimetric analysis (TGA). After b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Figure presented the C 1s , N 1s , O 1s , and P 2p spectra of the char residue. As shown in Figure A, the peaks at 286.1, 285.5, and 284.7 eV corresponded to the C─O, C─H, and C─C bonds, respectively . The N 1s spectra and the peak at 399.2 eV given in Figure B was assigned to C─N bond .…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Figure presented the C 1s , N 1s , O 1s , and P 2p spectra of the char residue. As shown in Figure A, the peaks at 286.1, 285.5, and 284.7 eV corresponded to the C─O, C─H, and C─C bonds, respectively . The N 1s spectra and the peak at 399.2 eV given in Figure B was assigned to C─N bond .…”
Section: Resultsmentioning
confidence: 91%
“…As shown in Figure 9A, the peaks at 286.1, 285.5, and 284.7 eV corresponded to the C─O, C─H, and C─C bonds, respectively. 29 The N 1s spectra and the peak at 399.2 eV given in Figure 9B was assigned to C─N bond. 10 The O 1s spectra was revealed in Figure 9C, and the peaks at 531.5, 532.8, and 533.7 eV were ascribed to C─O─C, P─O─P, and P═O bonds.…”
Section: Morphologies and Components Of Char Residuementioning
confidence: 97%
“…When 25 wt.% of them was added, the LOI value reached 28.8% with V-0 grade in UL-94 test. Moreover, Wang et al [ 99 ] synthesized a novel phosphorus-containing flame retardant (SPDH) via the interaction of synthesized intermediate product SPDPC with 10-(2,5-dihydroxyphenyl)-9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO-HQ). When the content of SPDH was 40 wt.%, an LOI value of 24.6% and a V-0 classification in UL-94 test were achieved.…”
Section: Organic Flame Retardantsmentioning
confidence: 99%
“…However, EVA is flammable and a melt dripping behavior can be observed along with the combustion , hence it is necessary for EVA to be incorporated with some flame retardant (FR) systems for reducing fire hazards and improving flame retardancy. As an effective FR, halogen‐containing FRs have been used in flame retarding materials . However, the obvious defects that releasing smoke and toxic gas limit their extensive use.…”
Section: Introductionmentioning
confidence: 99%
“…The IFR system is normally composed of three components: an acid source [e.g., ammonium polyphosphate (APP)], a carbonization agent [e.g., pentaerythritol], and a blowing agent (e.g., melamine) . Recently, as a novel HFFR intumescent additive, a char‐forming agent, a blowing agent and smoke suppressant, the graphite intercalation compound (GIC)—expandable graphite has been applied widely in the flame retarding polymers such as polyolefin blends , polylactide , poly (methyl methacrylate) , and particularly in polyurethane(PU) and PU coatings . Some researches found that the expandable graphite doped other traditional FRs, such as polyphosphate and layered double hydroxide, made PU exhibit a better flame retardancy, whose decomposition temperature, char residue, smoke release were affected by the additional FRs…”
Section: Introductionmentioning
confidence: 99%